Protective Effects of Water Extract of Morus Nigra L. on 6-Hydroxydopamine Induced Parkinson’s Disease in Male Rats - Seyed Ali Ziai; Zeynab Niknami; Sima Nasri; Mehrdad Roghani (Novelty in Biomedicine, 2018)
Background: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by progressive loss of dopaminergic neurons in the substantia nigra pars compacta. Although the etiology of PD is unknown, but major biochemical processes such as oxidative stress is largely described. Angiotensin II activates NADPH depending oxidases and produce superoxides formation. Morus nigra L. extract is an Angiotensin Converting Enzyme (ACE) inhibitor and tested for anti-Parkinsonism effects by biochemical and behavioral evaluations. Materials and Methods: In total 48 Male Wistar rats weighting 200-250 g were divided into 4 groups: (1) Sham (normal saline was injected in the left SNC), (2) Neurotoxin (injection of 6-hydroxydopamine into left SNC), (3) Morus nigra L. aqueous extract and (4) captopril. Morus nigra (10 mg/kg) and captopril (5 mg/kg) were daily-injected i.p. from 6 days before neurotoxin injection, until one day after 6-hydroxydopamine injection. Muscle stiffness and apomorphine test were assessed in 6 rats of any groups after two weeks. Protein oxidation, lipid peroxidation and ACE activity were assessed in brains of 6 rats of each group after 24 hours. Results: Rotation test with apomorphine, Rigidity with Murprogo’s test, and lipid peroxidation in sham, captopril and Morus nigra groups were significantly lower than neurotoxin group. Protein oxidation in Morus nigra group was significantly lower than neurotoxin group. Brain ACE activity in neurotoxin, captopril and Morus nigra groups were inhibited. Conclusion: Morus nigra L. extract had protective effects on neuronal oxidation and death and improved signs of PD possibly by ACE inhibition.